A Case Report : Comprehensive Treatment Approach Based on Endodontic and Periodontal Therapy - Naohiro, TOMINAGA; Taiki, KOBA; Nobuyuki, TANI-ISHII (The Japanese Journal of Conservative Dentistry, 2020)
Objective: It is difficult to make a diagnosis and treatment plan for clinical cases involving root fracture and endodontic/periodontal diseases because the relationship between clinical symptoms and causes is unclear. This time, we report a case in which comprehensive treatment based on endodontic and periodontal therapy was performed successfully for a patient who had a chief complaint of full-mouth dental therapy. Case: A 52-year-old female, with the chief complaint of full-mouth dental treatment at the first visit. After the completion of treatment, she moved to maintenance and hoped for occlusal recovery of the upper-left second molar (27). At the time of occlusal recovery, improvement of extension of 27, root canal treatment for periapical periodontitis, and implant treatment for 37 were required. Overview of first-stage treatment: As a basic treatment, the infected root canal was treated after periodontal treatment. For root bifurcation lesions of 36, periodontal regenerative therapy using autologous bone graft and EMD was performed. After the root canal treatment, crown lengthening surgery was performed for 26 in consideration of the final prosthesis, and the crown length extension and clearance were secured. Root fracture was observed in 23 and alveolar bone resorption was progressing, so the tooth was extracted and implant treatment was performed. After periodontal and root canal therapy, occlusal reconstruction treatment was performed on teeth 16-26 and 46-36. Overview of second-stage treatment: Since the patient hoped for occlusal recovery during the maintenance period, occlusal reconstruction treatment with infected root canal treatment for 27 and implant treatment for 37 were started. For 27, after performing root canal treatment under an operative microscope, an abutment was built and a crown lengthening operation was performed to secure clearance with a mating implant. The progress of infected root canal treatment of 27 was favorable, and the implant for 37 was placed with the superstructure aligned on the occlusal plane. After confirming the health of the upper and lower gingiva, superstructures for 27 and 37 were prepared and occlusal recovery up to 27 was completed. Currently, maintenance is being carried out continuously, and 4 years have passed since the end of treatment, with smooth progress. Conclusion: It is considered that the most important and final occlusal construction is smoothly guided by comprehensive basic treatment based on an exact preoperative diagnosis and treatment plan. It is considered that the operative dental microscope enables highly accurate treatment for infected root canals, crown restoration, and prosthodontic treatment, and contributes to the improvement of clinical results.